1989
DOI: 10.2307/3899230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Rate on Quantity and Quality of Available Forage in a Southern Mixed Grass Prairie

Abstract: The objective of tbie study ~8s to qu8ntify the long-term (25 ye8rs) effecte of be8vy (HC) 8nd modcnte (MC) r8te!3 of &ckin~ on qtmntity 8nd qtmlity of forage 8v8iLble. Study desip required frequent lmrvest of rt8nding crop on 5 r8np rite8 in twice rep& c8ted, 244 ha tre8tment p8eturee. Resulta from the 20montb study lowed 8boveground st8nding crop dynrrmke were aimil8r in botb trerrtments, qu8nthy of8v8ikbk fonp ~8s gre8ter in the MC tbrn HC tr#tment, qtmlity of l v8K8ble forye ~8s gre8ter generally ia tbe HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…This was expected since this species is known to decrease under heavy stocking (Heitschmidt et al, 1985(Heitschmidt et al, , 1989. It was more abundant on the clay-loam than on the shallow-clay soils.…”
Section: Discussionmentioning
confidence: 83%
“…This was expected since this species is known to decrease under heavy stocking (Heitschmidt et al, 1985(Heitschmidt et al, , 1989. It was more abundant on the clay-loam than on the shallow-clay soils.…”
Section: Discussionmentioning
confidence: 83%
“…The patterns of interspecific tiller defoliation observed in this study parallel the long-term patterns of grazing-induced species replacement observed in this grassland. Generally, BOCU decreases in absolute abundance, STLE and ARLO remain relatively constant and BUDA and HIBE increase dramatically with increasing grazing severity (Heitschmidt e/o/., 1985;1989). Shortgrass species were more leniently grazed than dominant midgrasses because a greater portion of their total lamina area was in close proximity to the soil surface (Fig.…”
Section: The Intensity Of Tiller Defoliation Wasmentioning
confidence: 99%
“…These activities continue through recent times (e.g. Heitschmidt et al, 1989;Ansley et al, 1998;Teague, 1999), resulting in landscapes comprised of a mosaic of Prosopis stands that vary in canopy cover, stature and stem density (Ansley et al, 2001;Asner et al, 2003).…”
Section: Study Areamentioning
confidence: 99%